PROFILE OF DIABETIC KETOACIDOSIS PATIENTS AT REGIONAL PUBLIC HOSPITAL DR. SOETOMO IN 2017 - Desak Gde Ushadi Bulan Dewata; Hermina Novida; Aryati Aryati (Jurnal Berkala Epidemiologi, 2020)
Background: Diabetic ketoacidosis (DKA) is one of many life-threatening complications of diabetes mellitus (DM), which is characterized by severe hyperglycemia, metabolic acidosis and ketonemia. This complication can eventually lead to coma and death if not treated properly. Purpose: The aim of this study is to describe the profile of the DKA patients who were at Regional Public Hospital (RSUD) Dr. Soetomo in 2017. Methods: This study was a descriptive study that used the medical record data of DKA patients who were at RSUD Dr. Soetomo in 2017. The study’s total sample size was 63 patients. The study’s variables were gender, age, type of DM, severity of DKA, precipitating factors, main complaints, vital signs, random plasma glucose level, electrolyte level, and blood gas analysis. The frequency, mean, and standard deviation were analyzed. Results: Most of the 63 DKA patients were female (66.67%), aged from 50–59 years (38.10%). The DKA cases being handled by the Dr. Soetomo Hospital were overwhelmingly of type 2 DM patients (88.89%). More than half the patients (58.73%) experienced severe DKA. Altered states of consciousness (46.03%) and shortness of breath (26.98%) were the most common main complains made by the DKA patients. Almost all patients experienced infection (88.89%) as the precipitating factor; the most common infections were sepsis (92.86%), pneumonia (30.36%), and urinary tract infections (23.21%). Two thirds of the patients (66.67%) had a length of stay of 0–7 days. About 57.14% of the DKA patients died while undergoing treatment. Conclusion: The number of severe DKA patients and the mortality rate in our study were higher than in other studies. Females and the elderly were more prone to DKA, and the most common precipitating factor was infection.